Neuro-Behçet: características imagiológicas. - Cristina Ramos; Goreti Sá; Vítor Tedim Cruz; Alexandra Lopes; João Xavier; Romeu Cruz (Acta Médica Portuguesa, 2006)
Behçet's disease is a chronic inflammatory, multisystemic disease of unknown aetiology. Central nervous system involvement occurs in a variable proportion of cases (4 to 49%) and is due to intracranial hypertension secondary to dural sinus thrombosis, inflammatory parenquimal lesions or recurrent meningoencephalitis. We reviewed 12 patients, 7 men and 5 women, aged between 27 to 40 years at the time of diagnosis. Neurological manifestations were secondary to parenquimal lesions in 7 patients, meningoencephalitis in 3 patients (including one with extensive medullary lesion) and dural sinus thrombosis in 2. Magnetic Resonance (MR) findings in Neuro-Behçet are non-specific. Nevertheless, MR has a role in characterizing brain lesions topography, helping in the diagnosis and in the follow-up of these patients.